TRANSLATION EQUIVALENCE OF INDONESIAN VERBREDUPLICATION INTO ENGLISH - NI PUTU AYU KARTIKA SARI DEWI (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
In terms of morphology, reduplication is called unique because it duplicates the similar words twice or more. In Indonesia, reduplication is often used in daily communication. It can make Indonesian language sound unique. It is possible to say “kecil-kecil” to emphasize “something (plural) in small size”. On the other hand, when Indonesian reduplication is translated into English, it is impossible to find “*small-small” as its translation. This paper aims to investigate about translation equivalence of Indonesian verb reduplication into English. The Natural Semantic Metalanguage approach proposed by Wierzbicka (1996) was used to find translation equivalence of Indonesian verb reduplication meaning and its translation into English. By using descriptive qualitative methods in analyzing data, the finding shows that verb reduplication emphasizes on reciprocal meaning, iterative meaning, and the meaning of doing something for happiness. Translating Indonesian verb reduplication into English means transferring the message or emphasizes meaning rather than preserving their unique form. Keywords: Reduplication, Translation Equivalence, NSM Approach